Use of a tourniquet in lower limb amputations: Evaluating blood loss in peripheral arterial disease patients A systematic review - Eldurssi, Omar (Division of General Surgery, 2023)
Background: Tourniquets have become an inseparable part of many different types of intricate and major surgeries, including amputation. Tourniquets create a bloodless environment, which is thought to facilitate surgery and reduce time, potential errors and subsequent complications. Objectives: To investigate the effectiveness of using a pneumatic tourniquet as an adjunct in lower limbs amputation in peripheral arterial disease to reduce blood loss and requirement for blood transfusions. Stump revision rate, complication and mortality will be assessed as secondary objectives. Method: For this systematic review, a search was performed using the keywords phrases, “peripheral arterial disease”, “lower limb amputation” and “tourniquet” in PubMed, Medline, Embase and Google scholar. Results: Based on univariate analysis, to determine the relationship between risk factors and blood loss, the study demonstrated the use of tourniquet significantly reduces the amount of blood loss during lower limb amputation (LLA), F (21.01), P=0.044. An independent t -test, demonstrated that there was a statistically significant difference in mean blood loss between tourniquet and non-tourniquet studies, (T=-2.588, P=0.049). In this review the mean blood loss was 251.67±2.89 and 462.5±137.69ml for tourniquet and non-tourniquet studies respectively. Conclusion: Using a tourniquet is a technically feasible approach to LLA, and effectively reduces the amount of blood loss and requirements of blood transfusion. No change in revision rates were noted.